Relationship Between The Anxiety Of Pregnant Women In Pandemic Time And Antenatal Care Visits In The UPTD Puskesmas Area, Gunungsitoli District - Yusni Widayati Harefa (International Journal of Health Engineering and Technology, 2023)
During the Covid-19 pandemic, there were many changes, especially in health services due to efforts to prevent transmission of Covid-19 so that pregnant women experienced anxiety about visiting health facilities for fear of contracting Covid-19 and in health facilities service restrictions were also carried out from the previous schedule. This study aims to analyze the relationship between the anxiety of pregnant women during a pandemic and antenatal care visits in the UPTD area of ​​the Gunungsitoli District Health Center. This research uses quantitative methods and is a type of non-experimental research, with a cross-sectional design. This research was conducted in the working area of ​​the Gunung Sitoli City Health Center, Nias, North Sumatra in December 2022. The subjects of this study were pregnant women. The sampling technique in this study used simple random sampling with a total of 232 pregnant women. The instrument used is a questionnaire. From the results of bivariable analysis using the Chi-square test the relationship between anxiety and the accuracy of ANC visits was obtained p = 0.015 (p <0.05). In conclusion, there is a significant relationship between anxiety and the accuracy of ANC visits.